(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article discusses the artistic depiction of children in modern Uzbek stories, the motif of “childhood”. We can see that the stories reflect the worldview, thinking, thoughts, desires, and aesthetic attitude of the younger generation to reality. Although most of them are created by experienced writers, reality is interpreted and studied from the perspective of children and told in their language. As each person lives, remembering his childhood and the beautiful memories associated with it, he involuntarily experiences sweet feelings. For a creator, childhood memories serve as a lifelong source of inspiration and material for his works. We can also find works reflecting the lives of children in the works of writers Erkin A’zam and Kamchibek Kenja. We can witness that childhood memories and motifs served as literary material in many of their stories. Writers in their stories focused on revealing the nature of the character, the human psyche, especially the subtle aspects of the child’s psyche. In particular, Kamchibek Kenja, while creating the image of a child, expresses the spiritual experiences, emotions, and events that shook them in the language of a child. This makes the story more vivid and touching for the reader. In general, the attitude to the image of children in Uzbek stories, changes in their worldview, the nobility of their character, purity, sincerity, and transparency in their interest in life attract the attention of any reader.